2012
DOI: 10.1007/bf03262308
|View full text |Cite
|
Sign up to set email alerts
|

Recovery in Soccer

Abstract: In elite soccer, players are frequently required to play consecutive matches interspersed by 3 days and complete physical performance recovery may not be achieved. Incomplete recovery might result in underperformance and injury. During congested schedules, recovery strategies are therefore required to alleviate post-match fatigue, regain performance faster and reduce the risk of injury. This article is Part I of a subsequent companion review and deals with post-match fatigue mechanisms and recovery kinetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
173
2
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(204 citation statements)
references
References 135 publications
12
173
2
17
Order By: Relevance
“…Nevertheless, future studies are needed to examine the reproducibility of this finding in diverse populations and to determine the threshold (intensity, volume, and weekly frequency) for intermittent exercise to enhance anti-inflammatory efficiency. RS resulted in significant increases in CK and LDH levels, in accordance with other studies conducted in participants of recreational (35) and competitive (15)(16)36) soccer matches. However, the blood kinetics of CK are somewhat higher and sustained in competitive players as compared with those in our recreational participants.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, future studies are needed to examine the reproducibility of this finding in diverse populations and to determine the threshold (intensity, volume, and weekly frequency) for intermittent exercise to enhance anti-inflammatory efficiency. RS resulted in significant increases in CK and LDH levels, in accordance with other studies conducted in participants of recreational (35) and competitive (15)(16)36) soccer matches. However, the blood kinetics of CK are somewhat higher and sustained in competitive players as compared with those in our recreational participants.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence indicates that the magnitude of force, the degree of lengthening, velocity of movement, and overall volume of eccentric load are probably the most important factors dictating the rate of muscle injury in response to exercise 146156. In fact, it has been shown that EIMD induced by a football match is associated with the number of explosive types of movement that incorporate a strong eccentric component 57,157…”
Section: Exercise-induced Inflammation and Sports Performancementioning
confidence: 99%
“…Consequently, monitoring the psycho-physiological response to training and competition, including the HPA axis, hypothalamic—pituitary—gonadal (HPG) axis and hypothalamic—pituitary—thyroid (HPT) axis has been seen within soccer [68]. Such HPT/HPA data has been used to determine player preparedness for subsequent training and competition, and inform individualized recovery strategies [911]. …”
Section: Introductionmentioning
confidence: 99%